PENGEMBANGAN MODEL LATIHAN MENYERANG PADA PERMAINAN BOLA BASKET - Iman Sulaiman; Ahmad Rizaldy Fajrin (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2018)
The objective of the research and development of the training model is to attack on the game of basketball. In addition, research and development is conducted to obtain in-depth information about the development and implementation of the exercise model and to know the effectiveness, efficiency of the model made.This research and development uses Research & Development (R & D) development methods from Borg and Gall. The subjects in this research and development are 2 different two place clubs of Victoria basketball club, Level Up basketball club.The model effectiveness test uses a test instrument to collect the basketball player's ability data. Analysis of research data using t test with significance level of 0.05. Analysis of data obtained average attack value before given model of attacking exercise is 61.0455 or 61 and after being given treatment with attacking model 75.5909 or 75.6. In the test of significance difference with SPSS 16 can result t-count = -29,567 db = 44 and p-value = 0.00 <0.05 which means there is a significant difference in the ability to attack before and after being given an attacking training model on basketball game that with a significance level of 0.05 then H0 is rejected. Based on the description it can be concluded that the training model attack on basket game developed that can be applied effectively and efficiently so that it can increase attack on basketball players.